Original paperAngiogenesis assessment in patients with mycosis fungoides - Jankowska-Konsur, Alina; Maj, Joanna; Woźniak, Zdzisław; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Mycosis fungoides (MF) is the most common primary cutaneous T-cell derived lymphoma. In the early stages the disease presents with erythematous, scaly macules and plaques. Similar lesions may appear in different skin conditions, such as parapsoriasis en grandes plaques (PP). Similarity of the clinical and partially the histopathological picture of both skin disorders prompts the search for a differentiating biomarker. Neoangiogenesis is a characteristic feature of malignant tumours such as solid tumours and haematological neoplasms. Aim: The aim of the study was to evaluate microvascular density (MVC) in the skin specimens obtained from skin lesions in the course of MF and PP. Material and methods: Immunohistochemistry studies were performed using antibodies to CD34. The MVC was assessed in 56 MF patients (29 patients with early disease (stage IA-IIA), 27 patients with advanced disease (stage IIB-IV) and 11 PP patients. The control group consisted of healthy individuals, patients of the Department of Plastic Surgery. Results: There was a statistically significant difference in MVC between the advanced MF group and both the early MF group and the PP group (p < 0.0001). There was no statistically significant difference between the early MF and PP group (p < 0.005), or between the early MF and PP groups and the control group. Conclusions: The studied factor does not fulfil the criteria for a biomarker distinguishing mycosis fungoides and parapsoriasis en grandes plaques, despite being a characteristic feature of advanced mycosis fungoides, and increased angiogenesis measured by CD34 expression is a poor prognostic marker of the disease.